Retained colistin susceptibility in clinical Acinetobacter baumannii isolates with multiple mutations in pmrCAB and lpxACD operons - Zafer, Mai M.; Hussein, Amira F. A.; Al-Agamy, Mohamed H.; Radwan, Hesham H.; Hamed, Samira M. (Frontiers in Cellular and Infection Microbiology, 2023)
The progressive increase in the resistance rates to first- and second-line antibiotics has forced the reuse of colistin as last-line treatment for Acinetobacter baumannii infections, but the emergence of colistin-resistant strains is not uncommon. This has been long linked to acquired chromosomal mutations in the operons pmrCAB and lpxACD. Hence, such mutations are routinely screened in colistin-resistant strains by most studies. The current study was designed to explore the possible existence of pmrCAB and lpxACD mutations in colistin-susceptible isolates. For this purpose, the whole genome sequences of eighteen multi-/extensively drug resistant A. baumannii were generated by Illumina sequencing and screened for missense mutations of the operons pmrCAB and lpxACD. Most of the isolates belonged to global clones (GCs) including GC1 (n=2), GC2 (n=7), GC7 (n=2), GC9 (n=3), and GC11 (n=1). The minimum inhibitory concentrations (MICs) of colistin were determined by the broth microdilution assay. Seventeen isolates were fully susceptible to colistin with MICs ranging from (≤0.125 to 0.5 µg/ml). Interestingly, all colistin-susceptible isolates carried missense mutations in pmrCAB and lpxACD operons with reference to A. baumannii ATCC 19606. Overall, 34 mutations were found. Most substitutions were detected in pmrC (n=20) while no mutations were found in pmrA or lpxA. Notably, the mutation pattern of the two operons was almost conserved among the isolates that belonged to the same sequence type (ST) or GC. This was also confirmed by expanding the analysis to include A. baumannii genomes deposited in public databases. Here, we demonstrated the possible existence of missense mutations in pmrCAB and lpxACD operons in colistin-susceptible isolates, shedding light on the importance of interpreting mutations with reference to colistin-susceptible isolates of the same ST/GC to avoid the misleading impact of the ST/GC-related polymorphism. In turn, this may lead to misinterpretation of mutations and, hence, overlooking the real players in colistin resistance that are yet to be identified.